Projeto e desenvolvimento de um dispositivo de montagem de implementos florestais - Souza, Anderson de (2021)
Brazil is one of the players in silviculture in the world, this fact has fostered the growth the demand of forestry implements in Brazil and thus increasing the competition among national and foreign manufacturers which also have come in search of a share of this market. Likewise, the proposal of the research is to deal about the improvement of the efficiency of the final equipment assembly in a Brazilian company that manufactures equipment for the mechanization of the forestry activity. The main objective of this work was the development of a device destined to the assembly of grapples, grapple saws and multifunctional heads to be used in forestry activities. The device was developed employing a method of design development and it proposes to identify the problems that cause a decrease in the process efficiency through the process supervising and measurement in the factory floor and the advisory to the professionals engaged in the final assembly reaching its top in the advancements in the process. The assembly equipment made the assembly process faster, safer and more ergonomic and it mostly also decreased the handling labor employed in the task. In the end of the work, it was also observed improvements in the finishing of the forestry equipment. In the end of the project, it was possible to observe the opportunity to develop an equipment for the assembly of other families of forestry implements, such as subsoilers and mini-skidders creating a similar equipment, but that simulates the three-point coupling system of agricultural tractors.